2006
DOI: 10.1177/0018726706068769
|View full text |Cite
|
Sign up to set email alerts
|

Toward the micro and macro-level consequences of interactional justice in cross-cultural joint ventures

Abstract: Nested within the logic of social exchange, this study addresses the micro-and macro-level consequences of interactional justice between boundary-spanning executives in cross-cultural joint ventures. At the micro-level, this study examines how interactional justice affects these executives' decision-making effectiveness and the interpersonal trust between boundary-spanning officers. At the macro-level, the study analyzes how interactional justice affects the levels of conflict and attachment between partner or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 69 publications
(90 reference statements)
0
32
1
Order By: Relevance
“…However, many researchers have focused on interactional justice as a single construct even after findings indicated that a two-factor solution should be adopted (e.g., George & Zhou, 2007;Luo, 2006Luo, , 2007. We believe that the apparent contradiction between our findings and those which obtained separate factors is primarily due to contextual differences which give rise to the halo effect.…”
Section: Implications For Theory and Researchcontrasting
confidence: 75%
See 1 more Smart Citation
“…However, many researchers have focused on interactional justice as a single construct even after findings indicated that a two-factor solution should be adopted (e.g., George & Zhou, 2007;Luo, 2006Luo, , 2007. We believe that the apparent contradiction between our findings and those which obtained separate factors is primarily due to contextual differences which give rise to the halo effect.…”
Section: Implications For Theory and Researchcontrasting
confidence: 75%
“…Colquitt's (2001) and Colquitt et al's (2001) view that interactional justice should be regarded as encompassing two factors is by no means universal in the current justice literature. Among the studies that have continued to reference interactional justice as a single construct those by Erdogan, Liden, and Kraimer (2006), George and Zhou (2007), and Luo (2006Luo ( , 2007.…”
Section: Research Questionsmentioning
confidence: 99%
“…It is focused on aspects of fairness related to interpersonal issues and information exchange in social context (Colquitt, 2001;Ariño & Ring, 2010), although it relates to the openness of communication among supply chain partners (Luo, 2007). Openness relates to greater sensitivity in managing conflict and disparities (Lu, 2006). Narasimhan et al (2013) found that justice is important for improving supply chain relationship performance and that each category of justice has unique contributions and an important part to play in supply chain relationships.…”
Section: The Relationship Between Supply Chain Justice Dimensions Andmentioning
confidence: 99%
“…Y. Luo (2006) studied firms from Europe, North America, and Asia Oceania making Chinese investments. Honesty and transparency (interactional justice) were found to buffer effects of cultural distance on trust and decision effectiveness for boundary-spanning executives and their Chinese partners at the microlevel and attachment between IJV partners at the macrolevel.…”
Section: Performance-related Outcomesmentioning
confidence: 99%